Impacto da Utilização do Biodiesel do Óleo de Mamona no Desempenho de Motores Diesel - Monteiro, Leonardo de Almeida (2013)
The use of renewable fuels, such as the biodiesel, can ease the demand of fossil fuel for the power generation and transportation fields in rural area. In this work, the performance impact of the application of castor oil biodiesel is evaluated with an automotive and a stationary diesel engine. The application of B20 and B10 biodiesel blends and pre-heated net biodiesel is considered. The viability of the employment of B10 and B20 blends to mobility and power generation was observed from dynamometric bench tests, where this blends performed similar to fossil diesel. With the pre-heated net biodiesel, however, a brake torque loss and a specific consumption increase were observed with relation to diesel fuel.